If the value of the above integral can be represented in the closed form as where and are co-prime integers, then evaluate .
Notations:
Check out this problem if you liked this one.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Lemma:
∫ 0 1 { k x 1 } d x = k − 1 k − ζ ( k )
∗ This implies that the value of our integral is 2 0 1 6 2 0 1 7 − ζ ( 2 0 1 7 ) , which gives a + b + c = 6 0 5 0 .
Proof:
Let
I = ∫ 0 1 { k x 1 } d x
Make the substitution t = x 1 , this gives d t = − x 2 1 d x and ∫ 0 1 ↦ ∫ ∞ 1 . So we get
I = ∫ 0 1 { k x 1 } ⋅ ( − x 2 ) ⋅ ( − x 2 1 ) d x = − ∫ ∞ 1 t 2 { k t } d t = ∫ 1 ∞ t 2 { k t } d t
Again make a substitution u = t k 1 , this gives d u = k 1 ⋅ t k 1 − k d t and ∫ 1 ∞ ↦ ∫ 1 ∞ . We get
I = ∫ 1 ∞ t 2 { k t } d t = ∫ 1 ∞ t 2 { k t } ⋅ k t k k − 1 ⋅ ( k 1 t k 1 − k ) d t = k ∫ 1 ∞ u 2 k { u } ⋅ u k − 1 d u = k ∫ 1 ∞ u k + 1 { u } d u = k ∫ 1 ∞ u k + 1 u − ⌊ u ⌋ d u = k ∫ 1 ∞ u k 1 d u − k ∫ 1 ∞ u k + 1 ⌊ u ⌋ d u = 1 − k k ⋅ u k − 1 1 ∣ 1 ∞ − k n = 1 ∑ ∞ ∫ n n + 1 u k + 1 n d u = 1 − k k ⋅ ( − 1 ) − k ( − k 1 ) n = 1 ∑ ∞ n ⋅ [ u k 1 ] ∣ n n + 1 = k − 1 k + n = 1 ∑ ∞ [ ( n + 1 ) k n − n k n ] = k − 1 k + ( 2 k 1 − 1 k 1 + 3 k 2 − 2 k 2 + 4 k 3 − 3 k 3 + ⋯ ) = k − 1 k + ( − 1 k 1 − 2 k 1 − 3 k 1 − ⋯ ) = k − 1 k − ζ ( k )
Q . E . D .